QOL-27. Sociocultural variables have a major impact on participation in patients treated for pediatric posterior fossa tumors. (3rd June 2022) - Hoffmann-Lamplmair, Doris; Gram, Alexandra; Krottendorfer, Kerstin; Peyrl, Andreas; Leiss, Ulrike; Czech, Thomas; Slavc, Irene; Pletschko, Thomas
Abstract: OBJECTIVE: This study investigates the extent of participation barriers in patients with pediatric posterior fossa tumors (PFTs) at long-term follow-up. While most studies focus on pathobiological variables that promote the occurrence of adverse late effects, the present analysis aims to investigate the importance of environmental variables. METHOD: Ten years after tumor diagnosis, 42 patients (mean age: 17 years) treated at our pediatric neuro-oncology unit were assessed for school and social difficulties using a questionnaire developed within the framework of this study. Participation barriers were assumed if patients and/or their parents reported difficulties at school or with peers. The children and adolescents were classified into groups with adequate and limited participation. Potential pathobiological (treatment type, hydrocephalus, tumor recurrence, gender, age at diagnosis, seizures, cerebellar mutism) and environmental risk factors (parental and maternal education, siblings, primary language, discrepancies between personal and environmental values, regular physical activity, private housing) were identified and examined to see if the participation groups differed in the amount of risk factors. RESULTS: Almost a decade after treatment, two thirds of the patients had school and/or social difficulties. Not only pathobiological risk factors (type of treatment, hydrocephalus, tumor recurrence, cerebellar mutism and seizures), but also environmental factors (low maternal education level, siblings, a main language other than German, discrepancies between social and personal values, and irregular physical activity) were associated with limited participation. These variables discriminated significantly between patients with and without participation barriers. CONCLUSION: Participation barriers in patients treated for pediatric PFT are frequent. In addition to pathobiological variables, environmental risk factors also play an important role in limiting school and social participation. This underlines the fact that a sole consideration of pathobiology is not sufficient when examining risk factors for the occurrence of late effects. The adoption of biopsychosocial perspectives in future studies is inevitable.